1999
DOI: 10.1177/0170840699204005
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Performance of Control

Abstract: Ideas about control are enriched by attending to cultural performances taking place in everyday organizational life. While much literature conflates culture with control, purists try to exclude control devices altogether, as if these artefacts cannot be expressive of real forms of culture. This view overlooks how managers make an `exhibition' of such artefacts on a daily basis in order to cut a figure of being `in' control. By closely examining which material is made visible and available, and when, the paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 20 publications
0
45
0
2
Order By: Relevance
“…A good public performance focuses attention on the subject, making one forget the media that make it possible. However, to understand how that very same cultural performance is produced and organised, what and who contribute and benefit, who are excluded, and what its exact effects are on the organisations involved, it is necessary also to look backstage to see the mundane events, hidden agendas, power struggles and the resource practices of everyday organisational life (Long, 1989;Law, 1994;Reed, 1992;Munro, 1999). On the basis of the episode observed above, it becomes evident what enables Nunez' public performance and his apparently spontaneous display of generous and charismatic leadership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good public performance focuses attention on the subject, making one forget the media that make it possible. However, to understand how that very same cultural performance is produced and organised, what and who contribute and benefit, who are excluded, and what its exact effects are on the organisations involved, it is necessary also to look backstage to see the mundane events, hidden agendas, power struggles and the resource practices of everyday organisational life (Long, 1989;Law, 1994;Reed, 1992;Munro, 1999). On the basis of the episode observed above, it becomes evident what enables Nunez' public performance and his apparently spontaneous display of generous and charismatic leadership.…”
Section: Discussionmentioning
confidence: 99%
“…These international policy events are analysed here as cultural performances that represent the success of the IMT model (Munro, 1999). They were carefully targeted, structured and arranged in order to appeal to a target group of key policy makers and persuade them to join in with 'the universal trend' to IMT/PIM.…”
Section: The Cultural Performance Of Success In Policy Eventsmentioning
confidence: 99%
“…Indeed, as I discuss in the next section on self, my ethnographic materials suggest people's attachment to cultural artefacts might be better understood as "cultural performance". 27 This is to note how alignment with the artefacts of certain technologies not only helps in "passing" as a member of this or that group, however poorly defined, but works also to make persons "visible and available" to the agendas of others. 28 Where displays of materials reflect asymmetries of power (and when would they not?…”
Section: The Turn To Culturementioning
confidence: 99%
“…Other ethnographic studies of organizations, although not focused on corridors, suggested that they were important sites not only for cultures of control, performance, and delivery, but also for informal information exchange and where anxiety and isolation became embodied (Fayard & Weeks, 2007;Michelson & Waddington, 2009;Munro, 1999;Sparkes, 2007;also Morrill & Fine, 1997;Brewer, 2004, for overview of ethnography in organization studies). In researching liminal space, I therefore had to learn how to read between the lines rather than seeking out a core of normalized, normalizing research practices, precisely because corridors are places where the building norms of an institution can be disrupted (Denzin, 2009).…”
Section: Design: the Power Of Corridorsmentioning
confidence: 99%